The Association of LDH Expression and Delayed Cerebral Ischemia in Patients with Aneurysmal Subarachnoid Hemorrhage: Possible Involvement of Cerebral Blood Perfusion - Wang, Yingwen; Tang, Shuang; Yang, Xiaomin; Cao, Yunchuan; Li, Xiaoguo; Xu, Rui; Yan, Jin; Guo, Zongduo; Sun, Xiaochuan; Wu, Yue (Current Neurovascular Research, 2023)
Background and Purpose: Several pieces of evidence suggest that serum lactate hydrogenase (LDH) level is associated with the pathological process of delayed cerebral ischemia (DCI) after aneurysmal subarachnoid hemorrhage (aSAH). This research aimed to investigate the associations of serum LDH level with the occurrence of DCI in aSAH patients. Methods: A total of 122 patients diagnosed with aSAH within 72h of onset were retrospectively enrolled. The serum levels of LDH between 7:00-8:00 am on day 1, day 3 and day 7, patients’ demographics, and clinical features were collected. Computed tomography perfusion was performed within 7 days after aSAH. The occurrence of DCI was recorded during the hospitalization. Results: Among all the enrolled patients, 43 (35.2%) developed DCI during hospitalization. Patients occurred DCI were always accompanied by more serious clinical features and found with higher serum LDH levels. LDH levels on day 3 and day 7 after onset were independently associated with the occurrence of DCI and showed high predictive value according to the receiver operating characteristic (ROC) curve. Moreover, there was a strong correlation between LDH and mean cerebral blood flow, transit time, and mean time to peak. Conclusion: Serum LDH level on day 3 and day 7 may be a valuable, convenient, and rapid predictive indicator for the occurrence of DCI in aSAH patients.
Keywords: EEG